Development of novel vaccine candidates and challenge models for Plasmodium vivax - Alves, E; Salman, A; Janse, C; Khan, S; Hill, A; Reyes-Sandoval, A (BioMed Central, 2014)
Plasmodium vivax is the most widely distributed human malaria parasite in the world and despite nearly 2.5 billion people living at risk, only four vaccines have been assessed in phase I clinical trials and only one has progressed to a phase II trial showing no sterile efficacy. We started to develop new challenge models to assess the efficacy of several new P. vivax pre-erythrocytic vaccine candidates (PVX_091700; PVX_121950; PVX_084090; PVX_099035; PVX_095375; PVX_000975; PVX_003665; PVX_000810) in mice. Our model is based on creating mutant P. berghei (rodent malaria) lines expressing P. vivax antigens through a new method called “Gene Insertion/Marker out” (GIMO). In addition, we are cloning the P. vivax pre-erythrocytic vaccine candidates in recombinant chimpanzee adenovirus (ChAd) and modified vaccine Ankara (MVA) vectors. Upon generation of transgenic parasites and recombinant viruses, a faster assessment to determinate the efficacy of all new P. vivax vaccine candidates can be achieved by using prime/boost immunization regimens followed by a challenge with corresponding transgenic chimera parasites.